Tissue composition and allometric growth of tissues from commercial cuts and carcass of Texel lambs slaughtered with different weights - Sérgio Carvalho; Luana Cortes Zago; Cleber Cassol Pires; Andressa Ana Martins; Rafael Sanches Venturini; Jusecléia Ferreira Lopes; Verônica Milanesi Pilleco; Robson Rodrigues Simões; Daniele Dias Brutti; Anderson Bortoluzi Moro (Semina: Ciências Agrárias, 2016)
In this study, we evaluated the tissue composition, the ratios between different issues, and the allometric growth of tissues from the commercial cuts neck, shoulder, rib, and leg, and of the carcass of Texel lambs. Thirty uncastrated male lambs born from single calvings were used in this experiment. Lambs were weaned, confined individually, and distributed into five treatments with six replications. Each treatment consisted of a predefined slaughter weight (T23 – initial slaughter, T25, T30, T35, and T40). The proportion of bone decreased linearly in the shoulder, rib, and legs, but remained constant in the neck. The proportion of muscle decreased in the rib, whereas in the other cuts it remained constant. The percentage of fat increased as the slaughter weight of the lambs was increased, for all cuts. In all cuts and in the carcass, bone and muscle showed early growth (b < 1), whereas fat displayed late growth (b > 1). The proportion of bone decreased and fat increased linearly in the carcass, and the proportion of muscle was not influenced by the slaughter weight of the lambs. The muscle/fat ratio decreased in all cuts, and consequently in the half-carcass, as the slaughter weight was increased. The muscle/ bone ratio increased in the shoulder, rib, leg, and half-carcass, but there was no significant effect on the neck. The bone and muscle tissues showed early growth, whereas the fat had late growth in the different commercial cuts and carcass of Texel lambs. The tissue growth pattern of the shoulder may be representative of the allometric growth of the different carcass tissues. An increase in the slaughter weight of Texel lambs leads to a reduction of the muscle/fat ratio, due to the higher deposition of fat in the carcass of these animals.